Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.9753/icce.v35.management.19
|View full text |Cite
|
Sign up to set email alerts
|

Model Versus Nature: Hydrodynamics in Mangrove Pneumatophores

Abstract: Water flows through submerged and emergent vegetation control the transport and deposition of sediment in coastal wetlands. Many past studies into the hydrodynamics of vegetation fields have used idealized vegetation mimics, mostly rigid dowels of uniform height. In this study, a canopy of real mangrove pneumatophores was reconstructed in a flume to quantify flow and turbulence within and above this canopy. At a constant flow forcing, an increase in pneumatophore density, from 71 m -2 to 268 m -2 , was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In a pilot study, we demonstrated that real pneumatophores may have a different effect on the flow dynamics when compared to published studies using dowel mimics [39]. However, the range of experimental conditions used in the published studies made it difficult to isolate and quantify differences.…”
Section: Highlights (85 Characters Each)mentioning
confidence: 73%
“…In a pilot study, we demonstrated that real pneumatophores may have a different effect on the flow dynamics when compared to published studies using dowel mimics [39]. However, the range of experimental conditions used in the published studies made it difficult to isolate and quantify differences.…”
Section: Highlights (85 Characters Each)mentioning
confidence: 73%
“…In some cases, for the smaller mangroves in New Zealand, the branches and leaves of the trees themselves are submerged during high tides, and therefore, once water levels reach the tree canopy, will likely enhance drag (as observed in similar mangroves in Japan and Vietnam (Chen et al 2016;Mazda et al 1997;Quartel et al 2007)) and possibly also generate additional turbulence. Whether these differences suggest that other factors such as sediment supply may play a stronger role in setting sediment deposition patterns than local turbulence conditions is an active area of research (see for example Horstman et al 2016;Horstman et al 2017). (Horstman et al 2017).…”
Section: Biophysical Interactionsmentioning
confidence: 99%
“…In some cases, for the smaller mangroves in New Zealand, the branches and leaves of the trees themselves are submerged during high tides, and therefore, once water levels reach the tree canopy, will likely enhance drag (as observed in similar mangroves in Japan and Vietnam (Chen et al 2016;Mazda et al 1997;Quartel et al 2007)) and possibly also generate additional turbulence. Whether these differences suggest that other factors such as sediment supply may play a stronger role in setting sediment deposition patterns than local turbulence conditions is an active area of research (see for example Horstman et al 2016;Horstman et al 2017). Figure 1) along (B) a transect covering tidal flat, fringe and mangrove forest (Horstman et al 2017).…”
Section: Biophysical Interactionsmentioning
confidence: 99%